2017
DOI: 10.1002/jcb.25836
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐101‐3p Regulates the Viability of Lung Squamous Carcinoma Cells via Targeting EZH2

Abstract: The aim of this study was to investigate the effects of miR-101-3p on the viability, migration, invasion, and mitosis of lung squamous carcinoma cells by inhibiting EZH2. In this study, RT-qPCR was used to detect the expression of miR-101-3p and EZH2 in both tissues and cells at RNA level. The dual luciferase reporter gene system was used to determine whether there was targeting relationship between miR-101-3p and EZH2-3'UTR. Western Blot was used to detect the expression of EZH2 as well as the proliferation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…Importantly, better overall survival rates and disease-free survival time of NSCLC patients correlated with higher miR-101-3p expression levels. Thus, miR-101-3p could act as a useful indicator for NSCLC outcomes, which is in consistency with other reports [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…Importantly, better overall survival rates and disease-free survival time of NSCLC patients correlated with higher miR-101-3p expression levels. Thus, miR-101-3p could act as a useful indicator for NSCLC outcomes, which is in consistency with other reports [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…In consideration of microRNAs paly their roles through regulating their target genes, such as miR-429 and BMI1 26, we predicted EZH2 gene might be a target of miR-101-3p by using online bioinformatics software. And, Hou Y reported miR-101-3p could regulate the proliferation of lung squamous carcinoma via targeting EZH2 27. EZH2 is an activator of gene expression, acting through multiple signaling pathways in distinct cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…We further demonstrated direct binding between miR-101-3p and MALAT1 by dual luciferase reporter and RIP assays. MiR-101-3p is a tumor suppressor, which promotes apoptosis of endothelial cells and affects viability and invasiveness of squamous cell carcinoma [ 29 33 ]. In this study, we demonstrated high MALAT1 and low miR-101-3p levels in lung cancer A549 and H1299 cells.…”
Section: Discussionmentioning
confidence: 99%